Integral Concept Learning through Number of Riemann Assisted by GeoGebra Software with a Creative Thinking Framework - Jarnawi Afgani Dahlan; Turmudi Turmudi; Alpha Galih Adirakasiwi; Lessa Roesdiana; Nurjanah Nurjanah; Hetty Patmawati; Nur Riski Hasanah (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2026)
This study aims to develop a contemporary learning design for definite integrals as a solution to challenges in mathematics learning. The integration of GeoGebra enriches students’ learning experiences, while a creative thinking framework supports the development of their creative skills. This design is expected to foster adaptive and innovative students who are prepared for future challenges. The study involved high school mathematics students and teachers and adopted the Plomp development model, including initial investigation, design, realization and construction, validation, and implementation phases. Data were analyzed using both qualitative and quantitative techniques to evaluate the validity, practicality, and effectiveness of the developed teaching materials. GeoGebra was utilized to create interactive simulations of Riemann sums, enabling students to manipulate partitions, interval lengths, and types of sums (left, midpoint, and right). These dynamic visualizations help students understand the limit process underlying definite integrals. The resulting learning design provides structured activities that guide students from visual exploration of area approximation to the formalization of the definite integral concept. The findings indicate that the developed teaching materials are valid, practical, and sufficiently effective in supporting students’ understanding of definite integrals through the concept of Riemann sums.